Breeding aims to develop sheep milk production - Kiss B.; Kovacs P.; Székelyhidi T.; Kukovics S. (Data collection and definition of objectives in sheep and goat breeding programmes: New prospects, 1997)
The Awassi Corporation imported 450 Awassi sheep from Israel in 1989-1990 to create a nucleus flock of a high yielding dairy sheep in Hungary. Based on this breed a three level (extensive, semi-intensive, intensive) production system was developed using the local Merino, Cigája and Racka breeds to find the best utilisation of their poor quality lands. On the basis of the experiences, an extensive dairy sheep farm integration model was developed, organising the breeding, technology and product marketing for the region.
Meeting of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats and Subnetwork on Animal Resources, 9-11 Mar 1997, Toulouse (France)